2005
DOI: 10.1074/jbc.m412280200
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and Template Nucleation of Self-Assembled Hydroxyapatite Nanocrystallites by Chondroitin Sulfate

Abstract: Biomineralization is an important process, which is often assisted by biomolecules. In this paper, the effect of chondroitin sulfate on the crystallization of hydroxyapatite was examined quantitatively based on a generic heterogeneous nucleation model. It is found that chondroitin sulfate can suppress the supersaturation-driven interfacial structure mismatch between the hydroxyapatite crystal and the substrate and promote the formation of ordered hydroxyapatite nanocrystallite assemblies. The nucleation mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
50
0
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(60 citation statements)
references
References 30 publications
2
50
0
1
Order By: Relevance
“…Growth of nano-hydroxyapatite (nHA) crystallites with various combinations of macromolecules and/or polymers have been performed by several others (Gower & Tirrell 1998;Gower & Odom 2000;Rhee & Tanaka 2000Olszta et al 2003a,b;Jiang et al 2005). Olszta et al (2003a,b) have shown that the synthesis of nHA in the presence of poly(aspartic acid) and poly(acrylic acid) proceeds with the formation of a fluid-like mineral precursor, which crystallizes into nHA within collagen fibrils.…”
Section: Introductionmentioning
confidence: 99%
“…Growth of nano-hydroxyapatite (nHA) crystallites with various combinations of macromolecules and/or polymers have been performed by several others (Gower & Tirrell 1998;Gower & Odom 2000;Rhee & Tanaka 2000Olszta et al 2003a,b;Jiang et al 2005). Olszta et al (2003a,b) have shown that the synthesis of nHA in the presence of poly(aspartic acid) and poly(acrylic acid) proceeds with the formation of a fluid-like mineral precursor, which crystallizes into nHA within collagen fibrils.…”
Section: Introductionmentioning
confidence: 99%
“…The role of various biological molecules as modulators of biomineralization has also been appreciated. PGs are involved in the calcification process acting either as promoters or inhibitors (31)(32)(33). PGs accumulated in the bone marrow in patients with MM may directly influence bone mineralization process.…”
mentioning
confidence: 99%
“…Effectively, the adsorbed organic molecules lead to a stronger interaction and a better structural fit between calcite and Na and Mg sulfates. 21 This model is very similar to the widely accepted model used to explain heterogeneous oriented nucleation of mineral phases assisted by organic molecules in biomineralization processes 71,72 and template-directed biomimetic mineral precipitation. 73 (f).…”
mentioning
confidence: 81%